(untitled) (The Research of Medical Science Review, 2025)
Background: Surgical careers demand precision, endurance, and unwavering commitment. However, the high-pressure environment, long working hours, and demanding workload can take a significant toll on the physical and mental well-being of surgeons. This study aims to assess how surgical duties affect surgeons' quality of life, focusing on physical and mental health, stress, burnout, job satisfaction, and work-life balance. It also explores the coping mechanisms and resilience strategies surgeons use to maintain their professional and personal well-being. Methods: A descriptive cross-sectional study was conducted at Ghurki Trust Teaching Hospital. A total of 105 surgeons participated. Data were collected using a validated, self-administered questionnaire that included 30 items on assessing quality of life. SPSS version 21.0 was used for data entry and statistical analysis. Descriptive statistics were used to report frequencies and percentages. Results: Out of 105 surgeons surveyed, a significant majority reported compromised quality of life due to their profession. Approximately 81.9% experienced high levels of stress, and 80% reported symptoms of burnout. 69.5% found it difficult to maintain work-life balance, while 89.5% indicated that their physical health had been negatively impacted. Mental well-being was also affected, with 76.2% experiencing symptoms of anxiety or depression. Furthermore, 75.2% of respondents felt pressured to work beyond their scheduled hours, and 54.9% considered their workload to be unmanageable. Despite these challenges, 92.3% remained committed to their surgical careers, though many sacrificed family time, hobbies, and sleep in pursuit of professional obligations. Conclusion: The findings highlight a high prevalence of stress, burnout, and work-life imbalance among surgeons. While most remain committed to their roles, the adverse impact on their health and quality of life is concerning. The study underscores the urgent need for institutional interventions such as wellness programs, stress management workshops, mental health support, and flexible scheduling to safeguard the well-being of surgeons and sustain the quality of patient care.